RELATIONSHIP BETWEEN 24-HOUR AMBULATORY BRACHIAL VERSUS AORTIC SYSTOLIC BLOOD PRESSURE AND LEFT VENTRICULAR MASS. THE INTERNATIONAL 24 HOUR AORTIC BLOOD PRESSURE CONSORTIUM. (June 2018) - Weber, T.; Wassertheurer, S.; Protogerou, A.; Sharman, J.; Sala, E. Rodilla; Jankowski, P.; Muiesan, M.L.; Giannattasio, C.; Wilkinson, I.; Hametner, B.; Pascual, J.M.; Zweiker, R.; et al.
Abstract : Objective: There is evidence of a closer relation between 24hour aortic systolic blood pressure (aSBP) and left ventricular mass (LVM) compared with 24hour brachial SBP. However, sample sizes are relatively small and there is some inconsistency in findings. We sought to address this by pooling data from 11 centers in Asia and Europe to determine the relationship between LVM and brachial office, as well as brachial and aortic 24hour ambulatory SBP. Design and method: In all centers, brachial and aortic SBP was measured with the same validated oscillometric device (Mobil-O-Graph, I.E.M. GmbH, Germany), using a transfer function for aortic pressure, and mean/diastolic pressure calibration. LVM was determined by echocardiography. Results: We studied 1299 participants (613 women) with a mean age of 50.8 years. Mean brachial office BP was 139/86 mm Hg, and mean 24hour bSBP and aSBP was 128 [127.3;128.7] and 131 [130.3;131.7] mm Hg, respectively. Mean LVM indexed to body surface area was 98 g/m2, and 34% of participants had left ventricular hypertrophy (LVH). The correlation coefficients between LVM and brachial office SBP, 24hour bSBP, and 24hour aSBP were 0.30, 0.35, and 0.42, respectively (P < 0.001 for comparison between brachial office SBP and 24hour aSBP and P = 0.01 for comparison between 24hour bSBP and 24hour aSBP). The areas under the curve for prediction of LVH were 0.634, 0.651, and 0.678 for brachial office SBP, 24hour bSBP, and 24hour aSBP, respectively (P = 0.004 for comparison between brachial office SBP and 24 h aSBP, and P = 0.001 for comparison between 24hour bSBP and 24hour aSBP) - Figure. Conclusions: In this pooled analysis of international data, we demonstrate that aortic ambulatory 24 hour SBP, measured with an oscillometric cuff, shows a significantly closer association with hypertensive cardiac organ damage (left ventricular mass and hypertrophy) than brachial office/brachial ambulatory systolic blood pressure. Figure. No caption available.